Characterization of the cardiorespiratory function and its relationship with oxidative stress in women exposed to wood smoke who live at high altitude (3,850 m a.s.l.) - Melgarejo-Pomar, Ingrid Gaby (2021)
Objective: To characterize the cardiorespiratory function and the state of oxidative stress resulting from the exposure to wood smoke in women who live at high altitude (3,850 m a.s.l.). Materials and methods: An observational case-series study. The cardiorespiratory function was analyzed, and thebiomarkers of oxidative stress malondialdehyde (MDA) and carboxyhemoglobin (COHb) were quantified. Measures of central tendency and dispersion were determined. The statistical methods of association and correlation were implemented. Results: Sixty (60) patients were included in the research. Fifty percent (50.00 %) of the participants showed clinical evidence of heart disease and 25.00 % had clinical symptoms of respiratory disease. Forty-five percent (45.00 %) of the spirometries revealed normal values. Thirty-six point six seven percent (36.67 %) showed a decrease in the forced expiratoryvolume in one second (FEV₁), forced expiratory volume in one second/forced vital capacity ratio (FEV₁/FVC) and/or forced expiratory flow 25-75% (FEF25-75). A decrease in FEV₁/FVC, FEF25-75 and FVC occurred in 8.33 %, 3.33 % and 1.67 % of the study participants, respectively. Moreover, a 5.00 % decrease was found in more than two parameters. Sixty percent (60.00 %) of the electrocardiograms revealed normal values, 36.67 % presented an intraventricular conduction disorder and 3.33 % showed dextrorotation of the heart. Eighty-one point six seven percent (81.67 %) of the participants presented an echocardiographic alteration, 73.33% showed valvular insufficiency, 20.00 % presented pulmonary hypertension and 6.67 % had an enlarged right ventricle. The mean MDA was 6 µM/L ± 2, which was positively correlated with the age (p: 0.029). The median COHb accounted for 1.00 % (p25: 0.70 – p75: 1.68). No statistically significant association was found between the COHb concentration and spirometric alterations. A positive correlation was found between MDA values and the right ventriclewall thickness (p: 0.001). Conclusions: The different alterations of the cardiorespiratory function found in the study population show that both chronic exposure to wood smoke derivatives and hypobaric hypoxia are an important source of free radicals and lead to a permanent and sustained state of oxidative stress, which is responsible for the progressive deterioration of the cardiorespiratory function with no early clinical manifestation.